An Efficient Clustering Algorithm in Wireless Sensor Networks Using Cooperative Communication. (9th June 2012) - Zhang, Shukui; Fan, Jianxi; Jia, Juncheng; Wang, Jin
Abstract : Processing the gathered information efficiently is a key functionality for wireless sensor networks. In generally, the sensor networks often use in-network data aggregation and clustering to optimize network communication. The set of aggregating nodes forms a dominating set of the network graph. Finding the weakly connected dominating set (WCDS) is a promising approach for clustering the WSN. However, finding a minimum WCDS is NP-hard problem for most graphs, and a host of approximation algorithm has been proposed. The aim of the paper is to construct a minimum WCDS as a clustering scheme for WSN. Our clustering schemes construction algorithm includes two phases. First of all, we construct a maximal data aggregation tree (DAT) of the network. The second phase of the algorithm is to choose the nodes (called connectors) to make the WCDS connected. The correctness and performance of our algorithms are confirmed through theoretical analysis and comprehensive simulations.